Two-stage heat-transfer modeling of cylinder-cavity porous magnetoelastic bodies - Elzayady, Mohamed E.; Abouelregal, Ahmed E.; Alsharif, Faisal; Althagafi, Hashem; Alsubhi, Mohammed; Alhassan, Yazeed (Mechanics of time-dependent materials, 2024)
This paper investigates the thermoelastic behavior of porous materials under magnetic fields using a dual-phase lag (DPL) model, with a specific focus on an unbounded porous body containing a cylindrical cavity. By applying the Laplace transform to address the time-dependent aspects of the governing equations, we investigate the effects of harmonically varying heat loads on the material’s porous–thermoelastic response. Numerical simulations provide insights into the distribution of excess pore water pressure, temperature, displacement, thermal stresses, and the magnetic field within the material. Results are presented through graphical analyses, facilitating a detailed comparison of porous–thermoelastic behaviors under different conditions. This approach not only validates the model’s accuracy but also enhances our understanding of porous materials’ responses to thermal and magnetic stimuli, offering valuable implications for their design and safety in engineering applications.